Perspektif Alkitab Tentang Ibadah Online - Indratno, Yohanes Twintarto Agus; Yohana, Yenny Herawati (CHARISTHEO: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This research explores the biblical perspective on the growing phenomenon of online religion in the digital age, where religious practices such as worship, Bible study, and fellowship are conducted virtually. Using qualitative methods and a biblical theology approach, this study analyses biblical texts and secondary literature to understand the compatibility of online religion with biblical principles. The results show that although online religion is not explicitly addressed in the Bible, the importance of physical fellowship in worship poses a theological challenge to the practice. However, online  religion can remain useful as an enabler of Christian community, especially in certain conditions where physical gathering is not possible.